Space Factors Influence on the Size Stability of Small Spacecraft Structure Elements. (2017) - Skvortsov, Yu.V.; Glushkov, S.V.; Chernyakin, S.A.
Abstract: This paper examines «Aist-2D» small spacecraft. Thermoelasticity problem is solved in two stages by finite element method using ANSYS® software. The first stage is thermal analysis. Space factors, devices and onboard equipment heat liberation are taken into account. External heat currents intensity and equipment work modes change depending on the spacecraft position on the Earth orbit. The second stage is stress-strain analysis of the structure, which is caused by the temperature field influence. As a result, the onboard equipment movement against structure elements and the acting forces are defined.